Pengaruh Social Media Marketing Activities Terhadap Keputusan Pembelian di Marketplace Shopee: Survei Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Makassar - Fikri Rahmat Utama; Chalid Imran Musa; Tenri S.P. Dipoatmodjo; Muhammad Ilham Wardhana Haeruddin; Muh. Ichwan Musa (PT Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of Social Media Marketing Activities (SMMA) in the form of Shopee COD advertisements on Purchase Decisions in the Shopee Marketplace. This type of research is quantitative with. the population is all students of the Faculty of Economics and Business, Makassar State University and a sample of 99 people. The data collection technique used is a questionnaire. The analytical method in this study uses instrument tests (validity test, reliability test), classic assumption test (normality test), coefficient of determination test, and t test. The results of the analysis found that Shopee Advertising SMMA had a positive and significant effect on decisions.